Efficient approach to analysis of TM modes in coaxial gyrotron cavity with corrugated insert - Tkachova, T.I.; Shcherbinin, V.I.; Tkachenko, V.I. (Вопросы атомной науки и техники, 2018)
Electromagnetic characteristics of TM modes of a coaxial gyrotron cavity with a corrugated inner conductor are investigated. Coupled-mode method based on re-expansion of the cavity fields in terms of the Gegenbauer polynomials is applied to reduce the computation time required for solving the eigenvalue problem with desired accuracy. Dispersion equation is obtained for calculating the eigenvalues of the TM modes. For these modes, transverse field distribution is investigated. Convergence of computations is shown for cavity eigenvalues and eigenfields. Досліджено електромагнітні характеристики ТМ мод в резонаторі коаксіального гіротрона з гофрованим внутрішнім провідником. Метод зв'язаних мод, заснований на перерозкладанні поля в резонаторі за поліномами Гегенбауера, застосовано з метою зменшення розрахункового часу цих характеристик з необхідною точністю. Отримано дисперсійне рівняння для власних значень ТМ мод. Для цих мод досліджено розподіл поля в поперечному перерізі резонатора. Показана збіжність розрахунків для власних значень та власних полів резонатора. Исследованы электромагнитные характеристики ТМ мод в резонаторе коаксиального гиротрона с гофрированным внутренним проводником. Метод связанных мод, основанный на переразложении поля в резонаторе по полиномам Гегенбауэра, применен с целью снижения времени расчета этих характеристик с требуемой точностью. Получено дисперсионное уравнение для собственных значений ТМ мод. Для этих мод исследовано распределение поля в поперечном сечении резонатора. Показана сходимость вычислений для собственных значений и собственных полей резонатора.